THE EFFECTIVENESS OF USING VIDEO YOUTUBE TOWARD STUDENTS’ SPEAKING ABILITY - Yunita, Lia Selfia (Jurnal Bahasa Lingua Scientia, 2015)
One of the media in globalization era in teaching speaking is video YouTube. Learning English by using YouTube will get a lot of benefits, learn the proper pronunciation of a word in a foreign language and make the material more quickly understandable. The research finding in this research is the mean score of speaking before being taught by using video YouTube is enough because the mean score of 16 students is 58.4375. After getting treatment, the mean score of speaking ability is 67.8125 based on the criteria of the students' score is good score it was improved, with the t-test analysis that used by researcher, the result of t Count is by comparing the t Table that she has got in SPSS 16.0, T Count 6.895 and value of t Table on the score table t 0,01 1.753 , its mean that t Count is much bigger than t Table ( t Count > t Table) = ( 6.895 > 1.753). It was concluded that video YouTube is effective media to improve the students’ speaking ability.